Investigation of Behavior of Nail-Supported Excavation in Weak Rocks by 1:1 Model Experiment - Cinar, Arif; Kilic, Havvanur; Berilgen, M. Mehmet (TURKISH CHAMBER CIVIL ENGINEERS, 2024)
This paper investigated the behavior of a nail-supported deep excavation in a weathered sandstone unit using a 1:1 scale field model experiment. The 1:1 scaled model experiment was designed by the limit equilibrium and numerical analysis considering the rock properties determined from the geotechnical investigations in the area. So the deep excavation supported by 5 vertical rows and 7 horizontal rows nail was made. The nails are built with 14 mm diameter ribbed construction steels, which are placed and injected into 13 cm diameter drilled holes at a 15(degrees) angle. The excavation was performed step by step after the nail construction and geotechnical observation were conducted. A pull-off test on a nail and unconfined compression tests on grout samples were performed to assess the test results better. The pull-off test was performed on a nail that was 28 mm diameter ribbed construction steel, and the strain gauges were placed on it. The data of the instrumental observations made under the excavation stages and the applied surcharge load were evaluated with graphics and drawings. In light of the evaluations, it was concluded that nails could be applied safely in weathered rock units and that the local and general stability of the nail-supported excavation design remains on the extremely safe side due to the rock characteristics that could not determined by detailed field and laboratory experiments.
Keywords: 1:1 model test; weak rock; deep excavation; instrumental observation; Engineering